Perancangan Buku Estetika Tato Dengan Teknik Fotografi Guna Meningkatkan Citra Tato Kepada Masyarakat - Kresnanda, Gede Bintang; Budiardjo, Hardman; Riyanto, Darwin Yuwono (Jurnal Art Nouveau, 2016)
Everything to do with tattoos, must relate to the criminal offense has been stuck in our minds. Bad image to those who have a tattoo on the body has confined the creativity of some people. The reason is, there is a presumption that all criminals caught certainly had marks on his body called tattoo. Tattoos have long known to humanity. That said, one of the expressions of tattoos as works of art has existed since several centuries BC in some tribes. Tattooing or body painting or tattoo is an image or symbol that is engraved on the skin using a needle similar tools. Usually, images and symbols that are decorated with colorful pigments. In the old days, people are still using manual techniques and traditional materials to tattoo someone. Now, people have been using the needle of iron, which is sometimes driven by the engine to